Equilibrium study of logistics demand and logistics resource allocation in Guangdong Province - Liu Lianhua; Wu Yanling; Lyu Shiqi; Chen Zexian (Scientific Reports)
Abstract Logistics serve as a vital link between production and consumption. The balanced allocation of logistics demand and resources can promote the harmonious development of the logistics system, thereby fostering regional economic growth. As a leading region in China’s reform and opening-up, Guangdong Province has experienced high economic growth. The equitable allocation of logistics demand and resources within a province is crucial for sustaining its economic development. This paper investigates the regional characteristics of logistics demand and resource allocation in Guangdong Province by analyzing the spatial distribution and evolutionary trends of logistics demand alongside the equilibrium of logistics resource allocation. First, the entropy weight method is utilized to examine the development trends of logistics demand and resource levels in Guangdong Province. Second, spatial autocorrelation analysis is applied to the spatiotemporal evolution characteristics of logistics demand across various cities in Guangdong Province for the years 2011, 2016, and 2021. Using 2021 cross-sectional data, an inconsistency index, which is based on geographic concentration, is employed to assess the mismatch between logistics demand and resource allocation across cities in Guangdong. The study reveals that logistics demand in Guangdong Province has been steadily increasing, with significant regional disparities. The spatial distribution exhibited a degree of correlation, with clustering patterns. However, logistics resource allocation remains imbalanced, with a certain degree of correspondence to logistics demand levels. Specifically, areas with higher logistics demand tend to have a higher concentration of logistics resources. The Pearl River Delta region holds the most abundant logistics resources, whereas many cities in northern and western Guangdong face severe shortages and are unable to meet the normal logistics demand.